Implementation Of The Principle Of Equal Rights For Persons With Disabilities In The Process Of Proceedings At The Purbalingga Religious Court - Muhammad, Syafik; Vauzi, Nur Kholis; Muzaki, Muhammad Zain; Malihatunnisa, Ade; Fatkhanah, Fatkhanah; Saputri, Apik Anitasari Intan; Ali, Nur (DAS Institute, 2025)
This study aims to analyze the implementation of the principle of equal rights for persons with disabilities in the litigation process at the Purbalingga Religious Court, as well as to formulate recommendations and concrete solutions to strengthen inclusive legal services. The research uses a qualitative approach with data collection techniques including interviews, observation, and documentation. The results show that the Purbalingga Religious Court has provided special services for persons with disabilities, reflecting the fulfillment of equal rights in legal proceedings. Recommendations include providing adequate physical access, enhancing the capacity of human resources to be more responsive to the needs of persons with disabilities, and drafting specific Standard Operating Procedures (SOP) for disability-friendly legal services. Concrete solutions that can be implemented include support services such as transportation for persons with disabilities, training court officers on inclusive services, and providing accessible infrastructure and facilities. Therefore, the implementation of the principle of equal rights in the judiciary can be realized in a tangible and comprehensive manner for all members of society, including persons with disabilities